Contrasting "back home" and "here": how Northeast African migrant women perceive and experience health during pregnancy and postpartum in Canada. Issue 1 (December 2016) - Quintanilha, Maira; Mayan, Maria; Thompson, Jessica; Bell, Rhonda
Abstract Background International migration and the number of migrant women who experience pregnancy and childbirth in receiving countries have significantly increased in the last two decades. Migrant women often have unmet social and economic needs during pregnancy, and are more likely to have problems unaddressed by health care systems. In this qualitative study, we explored migrant women's perceptions and experiences of health during pregnancy and postpartum, while participating in a perinatal program offered through a community-based organization. Additionally, we examined sociocultural factors that might have shaped women's health upon migration to the Canadian city of Edmonton, Alberta. Methods A community-based participatory research approach was used to engage migrant women connected to a community-based perinatal program in Edmonton. A focused ethnography was conducted with four Northeast African communities (Eritrean, Ethiopian, Oromo and Somali), and involved 10 focus groups with women (n = 8, per group) and direct observations of weekly perinatal program activities. Data generation and analysis occurred concurrently, and all generated data were analyzed using qualitative content analysis to inductively derive codes and categories. Results Women expressed their perceptions and experiences of health during pregnancy and postpartum by contrasting their countries of origin with Canada, respectively identified as "back home" and "here". Differences in social support and the physical environment (both natural and built) between "back home" and "here" were commonly described as factors that shaped their opportunities to eat healthy, be physically active and emotionally well before and after having a baby "here". Overall, women described that in Canada they lacked the social and environmental factors perceived as key enablers of healthy pregnancies and postpartum. Conclusion A complex network of factors seem to influence Northeast African women's health during pregnancy and postpartum upon migration to Canada. It is of the utmost importance to provide these women with the immediate sociocultural and environmental factors they need to successfully thrive during pregnancy and postpartum, especially while establishing social and support networks "here".